2002
DOI: 10.1089/089277902760367430
|View full text |Cite
|
Sign up to set email alerts
|

Single Upper-Pole Percutaneous Access for Treatment of ≥5-cm Complex Branched Staghorn Calculi: Is Shockwave Lithotripsy Necessary?

Abstract: Use of flexible nephroscopy with holmium:YAG laser lithotripsy and Nitinol basket stone extraction has allowed us to render staghorn-containing renal units stone free in a mean of 1.6 procedures. Of the 45 renal units treated through a single percutaneous access, 43 (95%) were rendered stone free. The holmium:YAG laser appears to be a safe lithotrite for the kidney, as no complications occurred from its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 15 publications
5
44
1
3
Order By: Relevance
“…Though mortality after PCNL is an extremely rare occurrence, AhmetTefekli et al 21 have reported one death in their series of 811 cases and there were no deaths during the postoperative period in our study.PCNL in ADPKD and horseshoe kidneys have been found to have a satisfactorystone-free rate and acceptable morbidity 22,23 . Though in our study there were only 4 horseshoe kidneys and 4 cases of ADPKD all these patients did not experience any increase in morbidity.…”
Section: Other Complicationssupporting
confidence: 48%
“…Though mortality after PCNL is an extremely rare occurrence, AhmetTefekli et al 21 have reported one death in their series of 811 cases and there were no deaths during the postoperative period in our study.PCNL in ADPKD and horseshoe kidneys have been found to have a satisfactorystone-free rate and acceptable morbidity 22,23 . Though in our study there were only 4 horseshoe kidneys and 4 cases of ADPKD all these patients did not experience any increase in morbidity.…”
Section: Other Complicationssupporting
confidence: 48%
“…[11][12][13][14][15] Upper calyx access is in the direction of the longitudinal axis of the renal pelvis and provides optimal sight from the upper pole to the lower pole and directly reaches the upper calyx, renal pelvis, uretero-pelvic junction and proximal ureter. 11,12,14,16 However, the risk of intra-thoracic complication increases with this access.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the collecting system is performed via upper, middle and lower calices. [11][12][13][14][15] Upper calyx access provides a perfect reach to the collecting system and many upper tract stones. However, this access may incur intrathoracic complications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations